A three-dimensional thick board pulp and preparation method thereof
The three-dimensional thick plate slurry prepared by mixing modified composite emulsions and aminolated silica coated with titanium carbide and other components, the limitations of existing printing materials in terms of three-dimensional effect, adhesion and durability are solved, and the good combination of printing materials and materials and the three-dimensional and durable effect of patterns are achieved.
Patent Information
- Application Number
- CN202410586871.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-05-13
AI Technical Summary
The existing printing materials have limitations in achieving three-dimensional effects, adhesion, durability and environmental protection, and are difficult to combine well with the printing materials, and the three-dimensional effects and durability of the printing patterns are not good.
The modified composite emulsion, aminolated silica coated titanium carbide, defoaming agent, leveling agent and thickening agent were used to prepare a three-dimensional thick plate slurry. Through the combination of these components, the adhesion and durability of the printing material were improved.
It achieves a good combination of printing materials and printing materials, improves the three-dimensional effect and durability of printing patterns, and also has excellent film forming performance, adhesion, firmness and wear resistance.
Smart Images

Figure CN118530618B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of printing materials, and in particular to a three-dimensional thick board pulp and a preparation method thereof. Background Art
[0002] Screen printing is a widely used printing technology, which is favored because it can be printed on a variety of materials, and has the advantages of fast printing speed, good printing effect, strong adaptability, etc. However, existing printing materials have limitations in achieving three-dimensional effects, adhesion, durability and environmental protection.
[0003] How to ensure the good combination of printing materials and printing materials, the three-dimensional effect of printed patterns and long-term durability are urgent problems to be solved. Therefore, developing a new type of screen printing paste to meet these specific needs has important practical value. Summary of the invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a three-dimensional thick board pulp and a preparation method thereof: adding a modified composite emulsion, amino-silica-coated titanium carbide, a defoaming agent, a leveling agent and a thickener into a mixer and mixing them evenly to obtain a three-dimensional thick board pulp, which solves the problems that the existing printing materials cannot be well combined with the printing materials, the three-dimensional effect of the printed pattern and the durability are poor.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A three-dimensional thick board pulp comprises the following components in parts by weight:
[0007] 45-65 parts of modified composite emulsion, 9-18 parts of amino silicon dioxide coated titanium carbide, 0.3-0.9 parts of defoamer, 0.2-0.8 parts of leveling agent and 0.1-0.5 parts of thickener;
[0008] Wherein, the modified composite emulsion is prepared by the following steps:
[0009] Step a1: adding hydrogenated silicone oil, p-divinylbenzene and toluene into a three-necked flask equipped with a stirrer and a thermometer, stirring the mixture for 25-35 min at a temperature of 50-55° C. and a stirring rate of 400-500 r / min, then adding chloroplatinic acid and heating the mixture to 90-95° C. and continuing to stir the mixture for 4-5 h. After the reaction is completed, cooling the reaction product to room temperature, and then removing the solvent by rotary evaporation to obtain vinyl silicone oil;
[0010] Step a2: adding methyl acrylate, butyl acrylate, hydroxypropyl acrylate, alkenyl silicone oil and deionized water into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stirring and reacting for 30-40 minutes at a temperature of 25-30° C. and a stirring rate of 400-500 r / min, then adding dibenzoyl peroxide and tert-butyl perbenzoate and heating to reflux and continuing stirring and reacting for 6-8 hours. After the reaction is completed, the reaction product is cooled to room temperature to obtain a composite emulsion;
[0011] Step a3: Add the composite emulsion, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stir the reaction for 2-3 hours at a temperature of 60-65°C and a stirring rate of 400-500r / min. Then, add methyl ethyl ketone oxime and continue stirring the reaction for 3-5 hours. After the reaction is completed, cool the reaction product to room temperature to obtain a modified composite emulsion.
[0012] As a further solution of the present invention: the usage ratio of the hydrogen-containing silicone oil, p-divinylbenzene, toluene and chloroplatinic acid in step a1 is 10 g: 0.8-3.2 g: 100-120 mL: 0.05-0.11 g.
[0013] As a further solution of the present invention: the hydrogen content of the hydrogen-containing silicone oil in step a1 is 0.372%.
[0014] As a further scheme of the present invention: the usage ratio of the methyl acrylate, butyl acrylate, hydroxypropyl acrylate, vinyl silicone oil, deionized water, dibenzoyl peroxide and tert-butyl perbenzoate in step a2 is 25-30g: 6.4-8.6g: 6.5-9.5g: 5.2-11.6g: 70-80g: 0.82-0.96g: 0.48-0.64g.
[0015] As a further solution of the present invention: the usage ratio of the composite emulsion, 4,4'-diphenylmethane diisocyanate, dibutyltin dilaurate and methyl ethyl ketoxime in step a3 is 10g: 0.95-1.35g: 0.01-0.03g: 0.5-2.5g.
[0016] As a further solution of the present invention: the amino-silicon dioxide-coated titanium carbide is prepared by the following steps:
[0017] Step b1: Add titanium carbide powder, deionized water and anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 2-2.5 hours under an ultrasonic power of 250-350W, then adjust the pH to 9-9.5 with a sodium hydroxide solution, then add tetraethoxysilane and stir the reaction for 3-5 hours at a temperature of 45-50°C and a stirring rate of 400-500r / min. After the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 4-5 hours to obtain silicon dioxide-coated titanium carbide;
[0018] Step b2: Place the silica-coated titanium carbide in a vacuum drying oven, dry it at a temperature of 100-110°C for 25-30 minutes, cool it naturally to room temperature, add it to a three-necked flask equipped with a stirrer and a thermometer, add toluene and ultrasonically disperse it at an ultrasonic power of 250-350W for 30-40 minutes, then add N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and deionized water and continue ultrasonically dispersing it for 5-8 minutes, then stir the reaction at a temperature of 70-75°C and a stirring rate of 400-500r / min for 3-5 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge it, place the precipitate in a vacuum drying oven, and dry it at a temperature of 60-65°C for 4-5 hours to obtain amino-silica-coated titanium carbide.
[0019] As a further solution of the present invention: the usage ratio of the titanium carbide powder, deionized water, anhydrous ethanol and tetraethoxysilane in step b1 is 1 g: 40-50 mL: 40-50 mL: 0.5-2.5 g.
[0020] As a further solution of the present invention: the mass fraction of the sodium hydroxide solution in step b1 is 20-25%.
[0021] As a further solution of the present invention: the usage ratio of the silica-coated titanium carbide, toluene, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and deionized water in step b2 is 1g:25-30mL:3-5mL:8-10mL.
[0022] As a further solution of the present invention: a method for preparing a three-dimensional thick board pulp comprises the following steps:
[0023] Step 1: Weigh 45-65 parts of modified composite emulsion, 9-18 parts of amino silicon dioxide-coated titanium carbide, 0.3-0.9 parts of defoamer, 0.2-0.8 parts of leveling agent and 0.1-0.5 parts of thickener according to weight parts, and set aside;
[0024] Step 2: Add the modified composite emulsion, amino-silica-coated titanium carbide, defoamer, leveling agent and thickener into a mixer and mix evenly to obtain a three-dimensional thick plate slurry.
[0025] As a further solution of the present invention: the defoamer is one of GP330 polyether defoamer and GPE50 polyether defoamer.
[0026] As a further solution of the present invention: the leveling agent is one of BYK-333 leveling agent and EFKA-3777 leveling agent.
[0027] As a further solution of the present invention: the thickener is one of HEC-506 thickener and PVOH-178 thickener.
[0028] Beneficial effects of the present invention:
[0029] The invention discloses a three-dimensional thick plate pulp and a preparation method thereof. Firstly, hydrogen-containing silicone oil and p-divinylbenzene are reacted, and Si-H on the hydrogen-containing silicone oil reacts with the alkenyl on the p-divinylbenzene to introduce the alkenyl to obtain alkenyl silicone oil. Then, methyl acrylate, butyl acrylate, hydroxypropyl acrylate and alkenyl silicone oil are used for emulsion polymerization to form a polymer containing hydroxyl and organic silicon to obtain a composite emulsion. Then, the composite emulsion and 4,4'-diphenylmethane diisocyanate are reacted, and the isocyanate group on the 4,4'-diphenylmethane diisocyanate reacts with the hydroxyl on the polymer in the composite emulsion. Reaction, thereby introducing isocyanate groups into the polymer, and then blocking it under the action of methyl ethyl ketoxime to obtain a modified composite emulsion, and then treating the titanium carbide powder with tetraethoxysilane, and the tetraethoxysilane is hydrolyzed under alkaline conditions to form silicon dioxide deposited on the surface of the titanium carbide powder to obtain silicon dioxide coated titanium carbide, and then the silicon dioxide coated titanium carbide is treated with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and the siloxane on the N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is hydrolyzed to form silanol grafted onto the surface of the silicon dioxide coated titanium carbide, At the same time, amino groups and secondary amino groups are introduced to obtain amino silicon dioxide-coated titanium carbide. Finally, the modified composite emulsion, amino silicon dioxide-coated titanium carbide, defoamer, leveling agent and thickener are added to a mixer and mixed evenly to obtain a three-dimensional thick plate pulp. The modified composite emulsion in the three-dimensional thick plate pulp contains organic silicon, which gives the printed pattern excellent softness and water-washing resistance, greatly improving its washing fastness. At the same time, the blocked isocyanate group is unblocked under the condition of heat treatment, giving it excellent adhesion, and reacting with the amino group on the amino silicon dioxide-coated titanium carbide to improve the bonding strength between the two. , so that the printed pattern has excellent adhesion. The amino silica-coated titanium carbide in the three-dimensional thick plate pulp is a composite structure of silica and titanium carbide, both of which have excellent mechanical properties. After adding it to the printed pattern, it can give it friction resistance. After amino modification, its dispersion performance is greatly improved, avoiding agglomeration to affect its reinforcement performance. The three-dimensional thick plate pulp finally prepared has excellent film-forming properties, adhesion, firmness and wear resistance, ensuring the close combination of the thick plate pulp and the printing material, and can meet various specific printing needs. At the same time, the preparation method is simple and easy, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention will be further described below in conjunction with the accompanying drawings.
[0031] Figure 1 The present invention is a flow chart of a method for preparing a three-dimensional thick board pulp. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] See also Figure 1 As shown, this embodiment is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0035] Step s1: 10 g of hydrogenated silicone oil with a hydrogen content of 0.372%, 0.8 g of p-divinylbenzene and 100 mL of toluene are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 50° C. and a stirring rate of 400 r / min for 25 min, then 0.05 g of chloroplatinic acid is added and the temperature is raised to 90° C. and the stirring reaction is continued for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain vinyl silicone oil;
[0036] Step s2: 25 g of methyl acrylate, 6.4 g of butyl acrylate, 6.5 g of hydroxypropyl acrylate, 5.2 g of vinyl silicone oil and 70 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 30 min. Then, 0.82 g of dibenzoyl peroxide and 0.48 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0037] Step s3: 10 g of the composite emulsion, 0.95 g of 4,4'-diphenylmethane diisocyanate and 0.01 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 60°C and a stirring rate of 400 r / min for 2 h, then 0.5 g of methyl ethyl ketoxime was added and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a modified composite emulsion;
[0038] Step s4: 1 g of titanium carbide powder, 40 mL of deionized water and 40 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 2 h at an ultrasonic power of 250 W, and then the pH was adjusted to 9 with a 20% mass fraction of sodium hydroxide solution, and then 0.5 g of tetraethoxysilane was added and stirred for 3 h at a temperature of 45 ° C and a stirring rate of 400 r / min. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 60 ° C for 4 h to obtain silica-coated titanium carbide;
[0039] Step s5: Place 1 g of silica-coated titanium carbide in a vacuum drying oven, dry at 100°C for 25 min, cool naturally to room temperature, add to a three-necked flask equipped with a stirrer and a thermometer, add 25 mL of toluene and ultrasonically disperse for 30 min at an ultrasonic power of 250 W, then add 3 mL of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 8 mL of deionized water and continue ultrasonically disperse for 5 min, then stir at 70°C and a stirring rate of 400 r / min for 3 h, after which the reaction product is cooled to room temperature and then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at 60°C for 4 h to obtain amino-silica-coated titanium carbide;
[0040] Step s6: weighing 45 parts of the modified composite emulsion, 9 parts of the amino-silica-coated titanium carbide, 0.3 parts of the defoamer, 0.2 parts of the leveling agent and 0.1 parts of the thickener according to weight; the defoamer is GP330 polyether defoamer; the leveling agent is BYK-333 leveling agent; the thickener is HEC-506 thickener;
[0041] Step s7: adding the modified composite emulsion, amino-silica-coated titanium carbide, defoamer, leveling agent and thickener into a mixer and mixing them evenly to obtain a three-dimensional thick plate slurry.
[0042] Embodiment 2:
[0043] See also Figure 1 As shown, this embodiment is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0044] Step s1: 10 g of hydrogenated silicone oil with a hydrogen content of 0.372%, 2.0 g of p-divinylbenzene and 110 mL of toluene were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 52° C. and a stirring rate of 450 r / min for 30 min, then 0.08 g of chloroplatinic acid was added and the temperature was raised to 92° C. and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain vinyl silicone oil;
[0045] Step s2: 28 g of methyl acrylate, 7.5 g of butyl acrylate, 8.0 g of hydroxypropyl acrylate, 8.4 g of vinyl silicone oil and 75 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 28° C. and a stirring rate of 450 r / min for 35 min. Then, 0.89 g of dibenzoyl peroxide and 0.56 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 7 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0046] Step s3: 10 g of the composite emulsion, 1.15 g of 4,4'-diphenylmethane diisocyanate and 0.02 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 62° C. and a stirring rate of 450 r / min for 2.5 h, and then 1.5 g of methyl ethyl ketoxime was added and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a modified composite emulsion;
[0047] Step s4: 1 g of titanium carbide powder, 45 mL of deionized water and 45 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 2.2 h at an ultrasonic power of 300 W, and then the pH was adjusted to 9.2 with a 22% mass fraction of sodium hydroxide solution, and then 1.5 g of tetraethoxysilane was added and stirred for 4 h at a temperature of 48 ° C and a stirring rate of 450 r / min. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 4.5 h to obtain silica-coated titanium carbide;
[0048] Step s5: Place 1 g of silica-coated titanium carbide in a vacuum drying oven, dry at 105°C for 28 min, cool naturally to room temperature, add to a three-necked flask equipped with a stirrer and a thermometer, add 28 mL of toluene and ultrasonically disperse for 35 min at an ultrasonic power of 300 W, then add 4 mL of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 9 mL of deionized water and continue ultrasonically disperse for 7 min, then stir and react at 72°C and a stirring rate of 450 r / min for 4 h, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, place the precipitate in a vacuum drying oven, and dry at 62°C for 4.5 h to obtain amino silica-coated titanium carbide;
[0049] Step s6: weighing 55 parts of the modified composite emulsion, 13 parts of the amino-silica-coated titanium carbide, 0.6 parts of the defoamer, 0.5 parts of the leveling agent and 0.3 parts of the thickener according to weight; the defoamer is GP330 polyether defoamer; the leveling agent is EFKA-3777 leveling agent; the thickener is HEC-506 thickener;
[0050] Step s7: adding the modified composite emulsion, amino-silica-coated titanium carbide, defoamer, leveling agent and thickener into a mixer and mixing them evenly to obtain a three-dimensional thick plate slurry.
[0051] Embodiment 3:
[0052] See also Figure 1 As shown, this embodiment is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0053] Step s1: 10 g of hydrogenated silicone oil with a hydrogen content of 0.372%, 3.2 g of p-divinylbenzene and 120 mL of toluene were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 55° C. and a stirring rate of 500 r / min for 35 min, then 0.11 g of chloroplatinic acid was added and the temperature was raised to 95° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain vinyl silicone oil;
[0054] Step s2: 30 g of methyl acrylate, 8.6 g of butyl acrylate, 9.5 g of hydroxypropyl acrylate, 11.6 g of vinyl silicone oil and 80 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 40 min, then 0.96 g of dibenzoyl peroxide and 0.64 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0055] Step s3: 10 g of the composite emulsion, 1.35 g of 4,4'-diphenylmethane diisocyanate and 0.03 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 65°C and a stirring rate of 500 r / min for 3 h, then 2.5 g of methyl ethyl ketoxime was added and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a modified composite emulsion;
[0056] Step s4: 1 g of titanium carbide powder, 50 mL of deionized water and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 2.5 h at an ultrasonic power of 350 W, and then the pH was adjusted to 9.5 with a 25% mass fraction of sodium hydroxide solution, and then 2.5 g of tetraethoxysilane was added and stirred for 5 h at a temperature of 50 ° C and a stirring rate of 500 r / min. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 h to obtain silica-coated titanium carbide;
[0057] Step s5: Place 1 g of silica-coated titanium carbide in a vacuum drying oven, dry at 110°C for 30 min, cool naturally to room temperature, add to a three-necked flask equipped with a stirrer and a thermometer, add 30 mL of toluene and ultrasonically disperse for 40 min at an ultrasonic power of 350 W, then add 5 mL of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 10 mL of deionized water and continue ultrasonically disperse for 8 min, then stir and react at 75°C and a stirring rate of 500 r / min for 5 h, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, place the precipitate in a vacuum drying oven, and dry at 65°C for 5 h to obtain amino silica-coated titanium carbide;
[0058] Step s6: weighing 65 parts of the modified composite emulsion, 18 parts of amino-silica-coated titanium carbide, 0.9 parts of a defoamer, 0.8 parts of a leveling agent, and 0.5 parts of a thickener according to weight; the defoamer is a GPE50 polyether defoamer; the leveling agent is an EFKA-3777 leveling agent; and the thickener is a PVOH-178 thickener;
[0059] Step s7: adding the modified composite emulsion, amino-silica-coated titanium carbide, defoamer, leveling agent and thickener into a mixer and mixing them evenly to obtain a three-dimensional thick plate slurry.
[0060] Comparative Example 1:
[0061] This comparative example is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0062] Step s1: 30 g of methyl acrylate, 8.6 g of butyl acrylate, 9.5 g of hydroxypropyl acrylate and 80 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 40 min, then 0.96 g of dibenzoyl peroxide and 0.64 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0063] Step s2: weighing 65 parts of the composite emulsion, 0.9 parts of the defoamer, 0.8 parts of the leveling agent and 0.5 parts of the thickener according to weight; the defoamer is GPE50 polyether defoamer; the leveling agent is EFKA-3777 leveling agent; the thickener is PVOH-178 thickener;
[0064] Step s3: Add the composite emulsion, defoamer, leveling agent and thickener into a mixer and mix them evenly to obtain a three-dimensional thick board slurry.
[0065] Comparative Example 2:
[0066] This comparative example is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0067] Step s1: 10 g of hydrogenated silicone oil with a hydrogen content of 0.372%, 3.2 g of p-divinylbenzene and 120 mL of toluene were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 55° C. and a stirring rate of 500 r / min for 35 min, then 0.11 g of chloroplatinic acid was added and the temperature was raised to 95° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain vinyl silicone oil;
[0068] Step s2: 30 g of methyl acrylate, 8.6 g of butyl acrylate, 9.5 g of hydroxypropyl acrylate, 11.6 g of vinyl silicone oil and 80 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 40 min, then 0.96 g of dibenzoyl peroxide and 0.64 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0069] Step s3: weighing 65 parts of the composite emulsion, 0.9 parts of the defoamer, 0.8 parts of the leveling agent and 0.5 parts of the thickener according to weight; the defoamer is GPE50 polyether defoamer; the leveling agent is EFKA-3777 leveling agent; the thickener is PVOH-178 thickener;
[0070] Step s4: Add the composite emulsion, defoamer, leveling agent and thickener into a mixer and mix them evenly to obtain a three-dimensional thick plate slurry.
[0071] Comparative Example 3:
[0072] This comparative example is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0073] Step s1: 10 g of hydrogenated silicone oil with a hydrogen content of 0.372%, 3.2 g of p-divinylbenzene and 120 mL of toluene were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 55° C. and a stirring rate of 500 r / min for 35 min, then 0.11 g of chloroplatinic acid was added and the temperature was raised to 95° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain vinyl silicone oil;
[0074] Step s2: 30 g of methyl acrylate, 8.6 g of butyl acrylate, 9.5 g of hydroxypropyl acrylate, 11.6 g of vinyl silicone oil and 80 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 40 min, then 0.96 g of dibenzoyl peroxide and 0.64 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0075] Step s3: 10 g of the composite emulsion, 1.35 g of 4,4'-diphenylmethane diisocyanate and 0.03 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 65°C and a stirring rate of 500 r / min for 3 h, then 2.5 g of methyl ethyl ketoxime was added and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a modified composite emulsion;
[0076] Step s4: weighing 65 parts of the modified composite emulsion, 18 parts of silicon dioxide, 0.9 parts of a defoamer, 0.8 parts of a leveling agent and 0.5 parts of a thickener according to weight; the defoamer is a GPE50 polyether defoamer; the leveling agent is an EFKA-3777 leveling agent; and the thickener is a PVOH-178 thickener;
[0077] Step s5: adding the modified composite emulsion, silicon dioxide, defoaming agent, leveling agent and thickener into a mixer and mixing them evenly to obtain a three-dimensional thick plate slurry.
[0078] Comparative Example 4:
[0079] This comparative example is a method for preparing a three-dimensional thick board pulp, comprising the following steps:
[0080] Step s1: 10 g of hydrogenated silicone oil with a hydrogen content of 0.372%, 3.2 g of p-divinylbenzene and 120 mL of toluene were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 55° C. and a stirring rate of 500 r / min for 35 min, then 0.11 g of chloroplatinic acid was added and the temperature was raised to 95° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain vinyl silicone oil;
[0081] Step s2: 30 g of methyl acrylate, 8.6 g of butyl acrylate, 9.5 g of hydroxypropyl acrylate, 11.6 g of vinyl silicone oil and 80 g of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 40 min, then 0.96 g of dibenzoyl peroxide and 0.64 g of tert-butyl perbenzoate were added and the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a composite emulsion;
[0082] Step s3: 10 g of the composite emulsion, 1.35 g of 4,4'-diphenylmethane diisocyanate and 0.03 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 65°C and a stirring rate of 500 r / min for 3 h, then 2.5 g of methyl ethyl ketoxime was added and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a modified composite emulsion;
[0083] Step s4: 1 g of titanium carbide powder, 50 mL of deionized water and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 2.5 h at an ultrasonic power of 350 W, and then the pH was adjusted to 9.5 with a 25% mass fraction of sodium hydroxide solution, and then 2.5 g of tetraethoxysilane was added and stirred for 5 h at a temperature of 50 ° C and a stirring rate of 500 r / min. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 h to obtain silica-coated titanium carbide;
[0084] Step s5: weighing 65 parts of the modified composite emulsion, 18 parts of silica-coated titanium carbide, 0.9 parts of a defoamer, 0.8 parts of a leveling agent, and 0.5 parts of a thickener according to weight; the defoamer is a GPE50 polyether defoamer; the leveling agent is an EFKA-3777 leveling agent; and the thickener is a PVOH-178 thickener;
[0085] Step s6: adding the modified composite emulsion, silica-coated titanium carbide, defoamer, leveling agent and thickener into a mixer and mixing them evenly to obtain a three-dimensional thick plate slurry.
[0086] The performance of the three-dimensional thick board pulp of Examples 1-3 and Comparative Examples 1-4 was tested. The three-dimensional thick board pulp was printed on cotton cloth by flat screen printing, with a drying temperature of 110°C, a drying time of 2 minutes, a baking temperature of 145°C, and a baking time of 3 minutes, and the printed pattern was tested. The test results are as follows:
[0087] sample Washing fastness after 20 times Dry rubbing fastness Feel Example 1 No change in flower pattern Level 5 Soft and smooth Example 2 No change in flower pattern Level 5 Soft and smooth Example 3 No change in flower pattern Level 5 Soft and smooth Comparative Example 1 Significant changes in flower shape Level 3 Soft and smooth Comparative Example 2 Slight change in pattern Level 3 Soft and smooth Comparative Example 3 No change in flower pattern Level 3-4 Soft and smooth Comparative Example 4 No change in flower pattern Level 4-5 Soft and smooth
[0088] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be learned that the use of modified composite emulsion and amino-silica-coated titanium carbide can effectively improve the fastness and friction resistance of three-dimensional thick plate pulp.
[0089] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0090] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A three-dimensional thick board pulp, characterized in that: It includes the following components by weight: 45-65 parts of modified composite emulsion, 9-18 parts of amino silicon dioxide coated titanium carbide, 0.3-0.9 parts of defoamer, 0.2-0.8 parts of leveling agent and 0.1-0.5 parts of thickener; Wherein, the modified composite emulsion is prepared by the following steps: Step a1: stirring and reacting hydrogenated silicone oil, p-divinylbenzene and toluene, then adding chloroplatinic acid and continuing stirring and reacting, cooling the reaction product after the reaction is completed, and then rotary evaporating to obtain vinyl silicone oil; Step a2: stirring methyl acrylate, butyl acrylate, hydroxypropyl acrylate, vinyl silicone oil and deionized water for reaction, then adding dibenzoyl peroxide and tert-butyl perbenzoate and continuing stirring for reaction, and cooling the reaction product after the reaction is completed to obtain a composite emulsion; Step a3: stirring the composite emulsion, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate to react, then adding methyl ethyl ketoxime to continue stirring the reaction, and cooling the reaction product after the reaction is completed to obtain a modified composite emulsion; Wherein, the amino-silicon dioxide-coated titanium carbide is prepared by the following steps: Step b1: ultrasonically disperse titanium carbide powder, deionized water and anhydrous ethanol, then adjust the pH with sodium hydroxide solution, then add tetraethoxysilane for stirring reaction, cool the reaction product after the reaction, then centrifuge, wash and dry the precipitate to obtain silicon dioxide-coated titanium carbide; Step b2: Dry the silica-coated titanium carbide, add toluene after natural cooling and perform ultrasonic dispersion, then add N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and deionized water and continue ultrasonic dispersion, then stir the reaction, and after the reaction is completed, cool the reaction product, then centrifuge it, and dry the precipitate to obtain amino silica-coated titanium carbide.
2. A three-dimensional thick board slurry according to claim 1, characterized in that: The usage ratio of the hydrogen-containing silicone oil, p-divinylbenzene, toluene and chloroplatinic acid in step a1 is 10 g: 0.8-3.2 g: 100-120 mL: 0.05-0.11 g.
3. The three-dimensional thick board slurry according to claim 1, characterized in that: The hydrogen content of the hydrogen-containing silicone oil in step a1 is 0.372%.
4. The three-dimensional thick board slurry according to claim 1, characterized in that: The usage ratio of the methyl acrylate, butyl acrylate, hydroxypropyl acrylate, vinyl silicone oil, deionized water, dibenzoyl peroxide and tert-butyl perbenzoate in step a2 is 25-30g: 6.4-8.6g: 6.5-9.5g: 5.2-11.6g: 70-80g: 0.82-0.96g: 0.48-0.64g.
5. The three-dimensional thick board slurry according to claim 1, characterized in that: The usage ratio of the composite emulsion, 4,4'-diphenylmethane diisocyanate, dibutyltin dilaurate and methyl ethyl ketoxime in step a3 is 10g: 0.95-1.35g: 0.01-0.03g: 0.5-2.5g.
6. The three-dimensional thick board slurry according to claim 1, characterized in that: The usage ratio of the titanium carbide powder, deionized water, anhydrous ethanol and tetraethoxysilane in step b1 is 1 g: 40-50 mL: 40-50 mL: 0.5-2.5 g.
7. The three-dimensional thick board slurry according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution in step b1 is 20-25%.
8. The three-dimensional thick board slurry according to claim 1, characterized in that: The amount ratio of the silica-coated titanium carbide, toluene, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and deionized water in step b2 is 1g:25-30mL:3-5mL:8-10mL.
9. A method for preparing a three-dimensional thick board pulp according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Weigh 45-65 parts of modified composite emulsion, 9-18 parts of amino silicon dioxide-coated titanium carbide, 0.3-0.9 parts of defoamer, 0.2-0.8 parts of leveling agent and 0.1-0.5 parts of thickener according to weight parts, and set aside; Wherein, the defoamer is one of GP330 polyether defoamer and GPE50 polyether defoamer; Wherein, the leveling agent is one of BYK-333 leveling agent and EFKA-3777 leveling agent; Wherein, the thickener is one of HEC-506 thickener and PVOH-178 thickener; Step 2: Add the modified composite emulsion, the amino-silica-coated titanium carbide, the defoamer, the leveling agent and the thickener into a mixer and mix them evenly to obtain a three-dimensional thick plate slurry.
Citation Information
Patent Citations
Organic silicone oil composite acrylic latex and preparation method thereof
CN114891166A
Epoxy resin composite material synergistically dispersed by modified silicon dioxide as well as preparation and application of epoxy resin composite material
CN115637021A
Curable resin composition for water repellent paint and coated material
JP2002114941A